Incidence and Prevention of Childhood Dental Caries-a review (Community Based Medical Journal, 2014)
Dental health problems are more common among the children and adolescent. A number of causes are behind it. Early childhood caries also calls baby bottle caries. Early childhood caries (ECC) is the presence of one or more decayed (non-cavited or cavited lesions), missing (due to caries) or filled tooth surface in any primary tooth in a preschool-age child as defined by- American Dental Association(ADA) and the term "severe Early childhood Caries (SECC) "refers to "Atypical" or "progressive" or "acute" or "rampant" patterns of dental caries. The severe early childhood caries (S-ECC) is due to low frequency and improper tooth brushing. Children of breast feed longer than one year and bottle feed containing carbohydrates specially at night are more affected. In low-income families, who consume snacks in high amount, bottle with sweetened drinks other than milk or water are more suffer. Early childhood caries (ECC) evolve with the factors like age start of brushing, lack of proper tooth brushing, Parental attitudes toward children's oral health, plaque on primary incisors at 1 year of age, over weight and obesity, Frequent consumption of cariogenic foods and bacterial infection, Feeding practices in the first year of life, not using of dental floss and presence of S. Mutans, Lacto-bacilli etc. Ethnic minority groups are also sufferer. Four predisposing risk factors are related to ECC- child's age, gender, age at weaning, and frequency of sweet drinks. Tooth brushing awareness among the children, Socio-economic upliftment, cultural and behavioral changes, Parenteral education, feeding practice, weaning at proper age, maintenance of oral hygiene, treatment of bacterial infection are essential for primary prevention of early childhood dental caries. Secondary prevention needs proper diagnosis and appropriate restorative treatment. Treatment modalities varies from severity of disease; temporary, permanent filling, crowning, root canal and treatment of complications.CBMJ 2014 July: Vol. 03 No. 02 P: 34-40